Stereologic measures of beta-amyloid load in postmortem autosomal dominant Alzheimer disease brain validate PiB-PET as a useful biomarker. (September 2019) - Sinha, N; Zhou, A; Li, Y; Joseph-Mathurin, N; Xiong, C; Morris, JC; Bateman, R; Benzinger, TL; Cairns, NJ; ,
Abstract : In vivo positron emission tomography (PET) using [C11]-labeled Pittsburgh Compound B ([C11]PiB) has previously been shown to detect amyloid-β (Aβ) in late-onset Alzheimer disease (LOAD) brain; however, the sensitivity of this technique for detecting β-amyloidosis in autosomal dominant Alzheimer disease (ADAD) has not been systematically investigated. To validate [C11]PiB PET as a useful biomarker of β-amyloidosis, we measured the cortical and regional standardized uptake value ratios (SUVRs) in 16 ADAD and 15 LOAD cases and compared them with histopathologic measures of β-amyloidosis in postmortem brain. The PiB-PET data were obtained between 40–70 min after bolus injection of ∼15 mCi of [11C]PiB. MRI and PiB-PET images were co-registered and SUVRs were generated for several brain regions. Using Aβ immunohistochemistry (10D5, Eli Lilly), the burden of Aβ plaques was quantified in 16 regions of interest using an area fraction fractionator probe (Stereo Investigator, MicroBrightfield, VT). There were regional variations in Aβ plaque burden with highest densities observed in the neocortical areas and the striatum. On spearman correlations, in vivo PiB-PET correlated with postmortem Aβ plaque burden in both LOAD and ADAD, with strongest correlations seen in neocortical areas. In summary, [C11]PiB-PET has utility as a biomarker in both ADAD and LOAD. LEARNING OBJECTIVES: This presentation will enable the learner to: 1. Discuss how PET-PiB beta-amyloid imaging is used as a potential biomarker of Alzheimer disease (AD) 2. Correlate postmortem neuropathologic evidence of beta-amyloidosis with PET-PiB data, and learn that PET-PiB is a potentially useful tool to detect beta-amyloidosis in presymptomatic and symptomatic individuals